Enhanced catalytic behaviour of surface dispersed nickel on LaCuO3 perovskite in the production of syngas: An expedient approach to carbon resistance during CO2 reforming of methane. (30th January 2016) - Touahra, F.; Rabahi, A.; Chebout, R.; Boudjemaa, A.; Lerari, D.; Sehailia, M.; Halliche, D.; Bachari, K.
Abstract: Perovskite oxide LaCuO3 and LaCu0.53 Ni0.47 O3 were prepared using the sol–gel citrate method, whereas 5% NiO/LaCuO3 was prepared by impregnation. The products obtained, after heat treatment under air at 800 °C, were characterized by several techniques such as: thermogravimetric analysis (TG), inductively coupled plasma atomic emission spectroscopy (ICP–AES), X-ray diffraction (XRD), Brunauer–Emmett–Teller method (BET) and temperature programmed reduction (TPR). After reduction, the catalysts were evaluated in the reforming of methane reaction under continuous flow with CH4 /CO2 ratio equal to 1, at atmospheric pressure and a temperature range [500–700 °C]. The catalytic activity was tested in a fixed bed reactor. At 700 °C, the amount of CH4 consumed was in its lowest in the presence of LaCuO3 whereas the amount of CH4 conversion increased to 60% in case of LaCu0.53 Ni0.47 O3 precursor. The best results were obtained using 5% NiO/LaCuO3 precursor, whereby the amount of CH4 consumed augmented by 16.5% compared to that of LaCu0.53 Ni0.47 O3 . Highlights: 5% NiO/LaCuO3 was synthesised using impregnation. LaCu0.53 Ni0.47 O3 was successfully synthesized using sol–gel method. The materials were applied as catalysts to generate syngas from methane reforming. 5% NiO/LaCuO3 shown high activity in syngas production compared to LaCu0.53 Ni0.47 O3 . 5% NiO/LaCuO3 resulted in less carbon deposition than LaCu0.53 Ni0.47 O3 .